ENHANCING EFL STUDENTS’ WILLINGNESS TO COMMUNICATE: TEACHERS’ BELIEFS ABOUT THEIR ROLES AND STRATEGIES - Funny Amalia Sari (Universitas Muhammadiyah Surakarta, 2016)
This study aims to investigate teachers’ beliefs about the scope of their roles in terms of interaction strategies in order to develop and maintain their learners’ willingness to communicate (WTC). Four experienced teachers of twoEnglish courses in Indonesia were asked to answer an open self-completion questionnaire that was designed based on the three interaction strategies proposedby Lee and Ng (2010). The study suggests any pedagogic interventions always depend on good teaching: one method alone does not promise success. This present study is expected to contribute to the comprehension of teachers’ influence to learners’ WTC particularly to language teacher development.